Anaerobic membrane bioreactors for treatment of emerging contaminants: A review. (15th September 2020) - Ji, Jing; Kakade, Apurva; Yu, Zhengsheng; Khan, Aman; Liu, Pu; Li, Xiangkai
Abstract: Emerging contaminants (ECs) are synthetic organic chemicals that released into the environment, which pose a serious threat to the ecosystem and human health. Due to the high costs of physicochemical methods and the possibility of secondary pollution, and conventional biological treatment techniques are not efficient to remove ECs. Thus, there is a need to develop novel technologies to treat ECs. Anaerobic digestion (AD) is reported to degrade most ECs. Anaerobic membrane bioreactor (AnMBR) is an upgraded AD technology that has high system stability and microbial community abundance. The biogas production and EC biodegradation efficiency in the AnMBR system are markedly higher than those in the traditional AD system. In recent years, AnMBR is widely used to remove environmental ECs. This review analyzes the feasibility and challenges of AnMBR in the treatment of ECs and provides useful insights for improving the performance and efficiency of AnMBR to treat ECs. Graphical abstract: Image 1 Highlights: Membrane modules retain biomass and increase biogas production. AnMBR improves the stability of anaerobic digestion reactor. AnMBR can removes different kinds of ECs and antibiotic resistance genes. The main mechanism of ECs removal by AnMBR is biodegradation.